The Politics of Presentation: On Badiou as Reader of Rousseau - Lorkovic, Edvard Marko (Cosmos and History: The Journal of Natural and Social Philosophy, 2012)
This paper explores the distinction between representative and presentative conceptions of politics in the works of Alain Badiou and Jean-Jacques Rousseau. Analyzing Badiou’s reading of Rousseau’s Social Contract, the paper shows that, contrary to a common view, Rousseau is not a normative theorist of legitimacy; instead, he is a political ontologist, one who thinks the being of politics rather than its norms. In this role, Rousseau defends a politics of presentation, a conception of politics as essentially creative rather than imitative. Against a view of politics as a representation of natural, divine or moral order, Rousseau’s political ontology maintains that politics exists only so long as order is created, out of nothing as it were. In short, politics cannot be representational; it exists only as long as it is present, not represented. For Badiou and Rousseau, representation is not necessarily illegitimate or unjust; it is simply not political.